Studies on the Arctic pack-ice habitat and sympagic meiofauna : seasonal and regional variabilities - Schünemann, Henrike (2004)
Sea ice is the main structural feature of polar seas. It plays an important role in energy transfer between the ocean and the atmosphere, but also serves as a natural habitat for a variety of organisms. Salt ions of the sea water are not included into the crystal structure of sea ice during freezing. These remain in the widely ramified system of brine channels within the ice. The brine channels are characterized by diameters of a few micro- to millimeters and provide a habitat for the so called sympagic (= ice associated) community. This association comprises bacteria, fungi, algae and protozoans, as well as metazoans. The investigated sympagic meiofauna of Artic pack ice mainly consists of copepods, nematodes, rotifers, turbellarians and nauplii. Late summer and winter pack ice of the central Arctic Ocean, the northern Fram Strait and the Storfjord (south of Spitsbergen) was sampled during three expeditions. The aim of this investigation was to evaluate the qualitative and quantitative composition of sympagic meiofauna as well as the controlling ice parameters of their distribution. Therefore, identical methods for sampling and sampling processing were used to obtain a comparison of seasonal and regional variability. This study presents for the first time an extensive, quantitative data set of environmental factors influencing composition, abundance and distribution of sympagic meiofauna organisms in wintertime Arctic pack ice. These data are compared with summer data of the same region. Additionally, the investigation of an extended area from south of Spitsbergen to the North Pole provides a unique base to evaluate regional variability of composition, abundance and distribution of sympagic meiofauna.